Morality and American Foreign Policy; The Role of Ethics in International Affairs - Robert W. McElroy (Princeton University Press, 2014)
FOR THE FIRST sixty years of this century, the question of what role morality plays in the formulation of foreign policy lay at the very heart of the scientific study of international relations. But during the past quarter century, in contrast, the role of morality in international affairs has been banished to the periphery of the field. Leading scholars may reject the charge that their scientific approaches to international relations lead to amoral conclusions, but they do not dedicate serious attention to investigating the influence of moral values on the conduct of nations.1 There are two major reasons for this transposition of the question of morality in the field of international relations. The first stems from the desire to establish the independence of the study of international affairs from all ethical and philosophical presuppositions, to construct a value-free science "consisting of formal models in which the preferences of the actors are treated as givens and in which attempts are made at quantifying the multiple unponderables of international affairs." 2 The second reason for the vanishing interest in the role of morality flows from the massive impact that realism has had in the field of international affairs. The realist tradition, which has remained the dominant paradigm in the study of international relations almost without interruption for the past thirty years, stresses the roles of necessity and anarchy in the politics of nations. In such a world of intense competition among nations, there is little room for meaningful choice on the part of state decision makers, and even less room for the choice of moral values that conflict with the national interest. But if the role of morality in the formulation of foreign policy has come to occupy a peripheral place in the field of international relations, it has become an ever more prominent part of the field of applied ethics. There has arisen in the past decade a vast new literature that investigates the moral choices inherent in foreign-policy decision making and offers prescriptions for ethical conduct in foreign affairs. In part, this literature has focused upon specific moral questions such as the deployment and use of nuclear weapons or the inequality in the distribution of resources among nations.3 But there has also appeared a series of more general theoretical treatments of the role of morality in foreign policy, treatments that grapple with the realist analysis of international relations and offer substantive non-normative criticisms of the realist worldview.